ANALISIS MATERI BAHASA ARAB DALAM BUKU AJAR KELAS 7 SMP MUHAMADIYAH AL FURQAN BANJARMASIN - Yusuf Hermansyah (Jurnal Al-Maqoyis, 2018)
The material in teaching is very important in the process of learning activities teaching, books have an important and dominant role in the learning process teaching in which the material to be discussed is described according to with the level, then in finding a good and appropriate textbook is very important needed. Although it is difficult to find a textbook that is perfect in its design but at least we must pay attention to the use of appropriate textbooks for taught, Neville Grant revealed that The perfect textbook does not exist, but the best book available for you and your students certainly does.